International airline alliances : EC competition law/US antitrust law and international air transport - Cheng-Jui Lu, Angela (Kluwer Law International The HagueNL, 2003)
Focuses on the relationship between competition law and the major economic activities of international airlines, such as the formation of alliances and the differences in and conflicts over various applications of divergent competition laws to airline alliances. Emphasizes the applications of EC competition law and US antitrust law to international airline alliances. Examines the differences in the relevant EC and US applications with regard to genesis, authorities, laws, procedures and policies. Explores the differences and conflicts between these two regimes. Identifies the essential elements in the liberalistion of international air transport and in the convergence of applications of divergent competitions laws to the economic activities of international airline alliances.